Advances in Water Resources and Hydraulic Engineering Proceedings of 16th IAHR-APD Congress and 3rd Symposium of IAHR-ISHS - Zhang, Changkuan; Tang, Hongwu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
"Advances in Water Resources and Hydraulic Engineering - Proceedings of 16th IAHR-APD Congress and 3rd Symposium of IAHR-ISHS" discusses some serious problems of sustainable development of human society related to water resources, disaster caused by flooding or draught, environment and ecology, and introduces latest research in river engineering and fluvial processes, estuarine and coastal hydraulics, hydraulic structures and hydropower hydraulics, etc. The proceedings covers new research achievements in the Asian-Pacific region in water resources, environmental ecology, river and coastal engineering, which are especially important for developing countries all over the world. This proceedings serves as a reference for researchers in the field of water resources, water quality, water pollution and water ecology. Changkuan Zhang and Hongwu Tang both are professors at Hohai University, China.
Water Resources and Hydrology -- Environmental and Ecological Hydraulics -- Fluvial Processes and River Engineering -- Estuarine and Coastal Hydraulics, Resttlement and Social Aspects -- Hydraulic Structures for Water Projects -- Hydropower Hydraulics.
Keywords: Engineering; Hydrology; Life sciences; Aquatic ecology; Engineering geology; Engineering -- Geology; Foundations; Hydraulics; Water pollution; Engineering; Geoengineering, Foundations, Hydraulics; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Life Sciences, general; Hydrology/Water Resources; Freshwater & Marine Ecology; Electronic books